PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI PECAHAN MELALUI MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA PESERTA DIDIK KELAS III SD NEGERI 06 NGRINGO KARANGANYAR - Ninda Beny Asfuri (JURNAL MITRA SWARA GANESHA, 2015)
AbstractThe purpose of the research is to improve mathematics learning outcomes through using of teaching model CTL at grade students of elementary school 06 Ngringo Karanganyar. The subject of this classroom action research is grade students of SDN 06 Ngringo Karanganyar, which consist of 38 students. Variable that are targeted to change in the research is improvement of mathematic in the topic of achievement of fraction. Whereas that are targeted to change in the research is teaching model CTL. The research is a classroom action research with 2 cycles. Every cycles consist of 4 phases, namely, planning, action, observation, and reflection. Variable data is sollected by using interview, observation, tes and documentation. Data analisys consists of data reduction, data presentation, and data verivication or conclusion drawing. The data validity used is substance validity and data result of the research, it can be conclude that the use teaching models CTL is able to improve of in the topic of achievement of fraction of grade student of elementary school 06 Ngringo Karanganyar. The increased can be seen from the result of math test of students who demonstrate improvemet that indicated and increase, namely, in pre-action is 63 with classical completeness 47,4%, in the cycle I, the average of classical score attains 69,7 and classical completeness increases to 77,9 and classical completeness increases to 97%. Therefore, it can be concluded that learning mathematic using teaching model CTL can improve learning outcomes to student′s grade students of elementary school 06 Ngringo Karanganyar.